Knowledge transfer intervention on flood risk reduction using flood learning education kit among school children in the Klang Valley, Malaysia - Azmi, Ezza Sabrina (2019)
Introduction: Investing in disaster risk reduction (DRR) for resilience community has been taken seriously worldwide by urging all parties, including local authorities, institutions, community and individual to devote in disaster risk education to proactively reduce and prevent disaster risks via structural and non-structural measures. Integrating DRR in schools would be helpful to inculcate disaster awareness culture in the community starting from children. Therefore, a sustainable disaster risk education via interactive knowledge transfer has seen as an important step to initiate awareness among children at the school level. Objective: This study aims to implement a knowledge transfer intervention by engaging children’s learning through an interactive learning education kit to enhance flood risk reduction knowledge transfer among school children. The effectiveness of this knowledge transfer was later compared with the traditional classroom-based teaching approach among school children. Methodology: A quasi-experimental study was designed to evaluate and compare the effectiveness of knowledge transfer on the flood disaster knowledge by using two teaching methods among school children which have been grouped into the experimental and control group. The experimental group was treated with the customized miniature of flood learning educational kit, and the control group was treated with a common teaching slide prepared using Microsoft PowerPoint. 352 children shall be recruited from eight selected primary schools in the Klang Valley area, which were calculated based on the sample size. By using a simple random sampling, a total of 337 school children were selected and recruited as the respondent from eight primary schools. The response rate obtained was 95.74%. The respondent for both groups was requested to complete a set of questionnaires twice (before and after the knowledge transfer intervention) to evaluate their baseline knowledge on flood risk reduction and their knowledge level following the intervention program. This questionnaire covered four parts of questions; Part 1: General knowledge on flood, Part 2: Flood warning and hazard, Part 3: Assembling flood emergency kit and Part 4: Readiness and responses to flood. Results: 71.8% of the respondents are ten years old students and another 28.2% are nine years old students. Among all the respondents, 55.8% are female students while 44.2% are male students. The majority of the respondents are Malay (97.3%), followed by Indians (1.5%), Chinese (0%) and other races (4%). By using a paired sample t-test, the result shows positive outcomes on knowledge level after conducting the intervention by using flood learning education kit. For the experimental group; the mean score shows a significant difference for all parts in the questionnaire with a mean difference of total score -6.048 (95% CI -7.532, -4.564; p<0.001). For the control group; the mean scores also show a significant difference for all parts in the questionnaire except for Part 4: Readiness and responses to flood with mean difference -0.168 (95% CI (- 0.778, 0.443; p=0.588) and total score -6.188 (95% CI -8.248, -4.127; p<0.001). ANCOVA was used to identify the effectiveness of both teaching method (learning education kit and traditional teaching method) to enhance the flood risk reduction knowledge level among school children in Klang Valley. After considered the influence of flood experience and pre-evaluation as a covariate, there is no significant difference between both methods with total score F (1,332) =0.024, p=0.877. Conclusions: This study shows that an effective educational approach will help to increase the knowledge of the learner. It is safe to conclude that, this interactive disaster learning kit on the flood disaster, was responsible for the knowledge improvement among the school children as the respondents of this study.